1996
DOI: 10.3109/00016349609054684
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery color Doppler assisted veloeimetry and perinatal outcome

Abstract: The addition of color Doppler imaging to pulsed wave Doppler ultrasound recording of uterine artery blood velocity improves the predictive value of blood velocity waveforms with regard to the perinatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 23 publications
3
65
0
1
Order By: Relevance
“…Hofstaetter et al reported uterine artery notch to be a better predictor of perinatal outcome than unilateral high PI. 15 This is in contrast to the findings of Ghosh et al where RI and PI were considered better indicators of vascular impedance in predicting adverse perinatal outcomes. 16 B/L notch in uterine artery Doppler was present in 25.4% participants and this findings are quit comparable with the similar study done by Wald RM et al, Rai L et al but not consistent with study done by Maria AL et al and Li H et al 11,13,14,17 Study found acceptable sensitivity, specificity, PPV and NPV of Doppler ultrasound during third trimester to predict obstetrical and perinatal outcome and this findings are comparable with study done by Rai L et al 13 Limitations of this study was number of cases has been small and study not included Patients who came in labor or with a complication like abruptio placenta.…”
Section: Discussionmentioning
confidence: 74%
“…Hofstaetter et al reported uterine artery notch to be a better predictor of perinatal outcome than unilateral high PI. 15 This is in contrast to the findings of Ghosh et al where RI and PI were considered better indicators of vascular impedance in predicting adverse perinatal outcomes. 16 B/L notch in uterine artery Doppler was present in 25.4% participants and this findings are quit comparable with the similar study done by Wald RM et al, Rai L et al but not consistent with study done by Maria AL et al and Li H et al 11,13,14,17 Study found acceptable sensitivity, specificity, PPV and NPV of Doppler ultrasound during third trimester to predict obstetrical and perinatal outcome and this findings are comparable with study done by Rai L et al 13 Limitations of this study was number of cases has been small and study not included Patients who came in labor or with a complication like abruptio placenta.…”
Section: Discussionmentioning
confidence: 74%
“…The transformation of subplacental arteries is normally complete at 20-24 weeks of gestation [16]. Impedance in the uterine artery decreases gradually during vessel transformation and is stable after 24 weeks of gestation in normal pregnancy [17,18]. Increased uterine artery impedance beyond 20-24 weeks of gestation has been reported to reflect abnormal placentation and relate to the development of preeclampsia [19].…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, Doppler sonographic examination of the uterine and umbilical arteries is instrumental for monitoring fetal well-being [30,31]. The hemodynamic parameters are interpreted in relation to the stage of gestation.…”
Section: Analysis Of Sonographic Measurementsmentioning
confidence: 99%